1996
DOI: 10.1017/s0266462300010989
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Economic Evaluation of the FIRST Study:A Multinational Prospective Economic Evaluation

Abstract: We present the prospective economic evaluation that served as a secondary endpoint for the FIRST study, a randomized international multicenter trial of patients with severe congestive heart failure. Although the clinical results of this study were disappointing, we demonstrated the feasibility of incorporating prospective economic evaluation in phase III clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 12 publications
0
34
0
1
Order By: Relevance
“…53,77,84 Furthermore, it has been argued that, in multinational trials, unit costs should be taken from all or a sample of centres within each country as applying unit costs from single centres in a multinational economic evaluation may reflect neither the average unit costs within a country nor the true variation in unit costs. 34 In a recent simulation exercise, it was confirmed that there is a significant difference in overall cost results between using unit costs averaged across centres and centre-specific costs to value all the resource use measured in the trial. 119 Frequently, unit costs may not be available for some sites in a study.…”
Section: Unit Costsmentioning
confidence: 96%
See 3 more Smart Citations
“…53,77,84 Furthermore, it has been argued that, in multinational trials, unit costs should be taken from all or a sample of centres within each country as applying unit costs from single centres in a multinational economic evaluation may reflect neither the average unit costs within a country nor the true variation in unit costs. 34 In a recent simulation exercise, it was confirmed that there is a significant difference in overall cost results between using unit costs averaged across centres and centre-specific costs to value all the resource use measured in the trial. 119 Frequently, unit costs may not be available for some sites in a study.…”
Section: Unit Costsmentioning
confidence: 96%
“…A random effects model was used to account for institutional variation in overall clinical results. In another multinational trial, Schulman and colleagues 34,77 attempted to quantify resource utilisation and quality of life in a population with severe congestive heart failure and to explain the variation among patients receiving epoprostenol therapy versus best usual care alone in 14 countries. The study concluded that the validity of estimates of the costs and their differences may be limited, because they were determined within the environment of a Phase III trial and because the application of a single set of unit cost data would not demonstrate the true variation in unit cost estimates between locations.…”
Section: Studies Looking At International Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…As recently reported, 23 this method adjusts for differential right-censoring by reweighting the observed costs and quality-adjusted life-months (QALMs) of patients followed in the later study period and predicting the costs and QALMs of study participants as if they had all been available for the full 13 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%